BUDAYA ORGANISASI MENUJU BUDAYA SEKOLAH YANG BERMUTU - Ismail Hardi (Hijri, 2019)
One of the functions of the school is to maintain the culture that exists in thecommunity. The school also functions to develop new cultural values that will keeppace with the changing times that enable young people to compete in a globalsociety. Schools must be able to ensure that the organizational culture that runs inthe school can create an organizational culture that is conducive to the growth anddevelopment of a good culture so that all personnel in the school can develop aquality culture. The quality of education can be achieved by implementing a wellmanagedcurriculum.